The first clinical case of heart transplantation in the Far Eastern Federal District - P. I. Zakharov; P. P. Portnyagin; V. S. Sivtcev; S. V. Lomonosov; V. I. Pavlov; D. A. Danilov; A. G. Nikolaev; D. V. Vasilev; A. S. Korostelev (Вестник трансплантологии и искусственных органов)
The first case of heart transplantation in the Far Eastern Federal District described. Transplantation of heart is executed in Republican hospital No. 1 - the National center of medicine (Yakutsk) on July 6, 2018. In our opinion, transplantation of heart is necessary and feasible in such regions as the Republic of Sakha (Yakutia) which have difficult and extreme climate and geography, remote settlements with population less than 1 million people.